Analysis of duplicate words in the short story of “Love You Forever” authored by Chanthy Duensavanh: https://doi.org/10.69692/SUJMRD080211 - DUANGCHAN, Boy; SISOUPHAN, Sangkhom; KHAMSAVHAN, Dalavone; SAYVONGSAN , Chanphathone; BOUNMALEUT, Daophet (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
In a study, the researchers have focused on two-syllable duplicate words of the short story “Love You Forever” authored by Chanthy Duensavanh. The objective of the research is to study the structures and compliment characteristics of two-syllable duplicate words used in the story. The methodology of the research is qualitative, and the results have been reported through analysis and interpretation. Remarkably, two-syllable duplicate words used by the writer, Chanthy Duensavanh, have an appropriate meaning for various situations. The researchers have found that, for two-syllable duplicate words, a total of 55 words with 3 different construction types:16 words of a noun-type structure (equal to 29.09%). In this type, 3 various constructions were evident: the noun and noun model type, the noun and verb model type, and the noun and adjective model type. 26 words (equal to 47.27%) were constructed as verb-type structures. The verb type includes 2 model types: verb and verb model type and verb and adjective model type. Researchers have also found 13 words (equal to 23.63%) of adjective type, which includes 3 model types: adjective and noun, adjective and verb, and adjective and adjective. The structures of duplicate words of the verb type occurred more other types. Regarding the compliment characteristics, the two-syllable duplicate words in the short story “Love You Forever” had three different characteristics: those with the same meaning (a total of 29 words, or 52.72%); those with a similar or opposite meaning (a total of 26 words, or 45.45%); and those with an opposite meaning (only 1 word, or 1.81%). Duplicate words with a similar meaning were used more when compared to other compliment types.